Typology of modern theoretical concepts of cultural economy - I. I. Parkhomenko, (Ukrainian Cultural Studies, 2018)
The article proposes theoretical concepts typology of the modern cultural economy, which proves the existence of economic relations in the field of culture according to the Western European scientific tradition of XX-XXI centuries: 1) cultural and philosophical (T.W.Adorno, J. Baudrillard, P.Bourdieu, M.Horkheimer, S.Lash, C.Lury, J.Urry); 2) cultural industries approach (R.Williams, B.Miege, N.Garhnam, P.L.Sacco); 3) economic and managerial (W.J.Baumol, W.G.Bowen, M.Blaug, V.A.Ginsburg, D.Hesmondhalgh, A.Klamer, B.Miege, A.J.Scott, D.Throsby, B.S.Frey). According to these modern theoretical concepts, culture is the sphere of production and consumption of goods and services; it is functioning as a resource for economic, social and cultural development. This understanding of culture is the basis of the current policy of cultural and creative industries in the European Union and the United Kingdom. Cultural production is an interdisciplinary object of study, since the cultural good has its own peculiarity: its cultural value determines economic value. The article analyzes production in the field of culture and, at first, determines economy of culture as a scientific approach for understanding the functioning of the modern society in the categories of production and consumption; secondly, economics of culture is a scientific discipline in the field of economics. Theoretical and methodological bases were interdisciplinary scientific approaches to the understanding of culture as a sphere of production and consumption. For that reason were organized and systematized approaches to the understanding of culture as an economic reality in scientific discourse: 1) critical theory of T.W.Adorno, W.Benjamin and M.Horkheimer and the concept of "cultural industry"; 2) the interaction of cultural and power institutions in the processes of democratization of society and industrialization of culture (R.Williams, N.Garhnam, P.L.Sacco); 3) culture as a set of cultural industries, which form cultural capital (P.Bourdieu, D.Hesmondhalgh, B.Miege, D.Throsby); 4) the functioning of modern society as global culture industry in theory of S.Lash and C.Lury; 5) cultural economics theory (W.J.Baumol, W.G.Bowen, M.Blaug, V.A.Ginsburg, A.J.Scott, D.Throsby, B.S.Frey).
Keywords: economy of culture, cultural production, cultural industries, industrialization of culture, value, theoretical concepts of the cultural economy